Real-Time Multi-User Video Optical Wireless Transmission Based on a Parallel Micro-LEDs Bulb - Zixian Wei; Zhongxu Liu; Zhaoming Wang; Mutong Li; Chien-Ju Chen; Meng-Chyi Wu; Songping Mai; Faisal Nadeem Khan; Changyuan Yu; H. Y. Fu (IEEE Photonics Journal)
In this work, we experimentally achieved a real-time video optical wireless transmission which can broadcast two users in different positions, simultaneously. Firstly, a single-pixel 50-μm micro-LED is designed and fabricated on a GaN-based wafer and then two micro-LED chips are connected as parallel form in a single bulb. The transceiver based on two FPGA boards is used to generate quadrature amplitude modulation-orthogonal frequency division multiplexed (QAM-OFDM) signals and measure the communication performance of the VLC system. The low-power micro-LEDs bulb emits 0.8 mW optical power through two optical paths at 20 mA driving current, and the modulation bandwidths for two users’ access are 90 MHz and 73 MHz, respectively. In this two-user real-time video transmission system, the total data rate exceeds 105.54 Mbps without naked eye discernable distortion over 2-m free-space distance. Different from traditional point-to-point links, this work demonstrates the possibility of flexible high-speed multi-user real-time video optical wireless transmission based on a parallel micro-LEDs bulb.